2022
DOI: 10.1097/md.0000000000028878
|View full text |Cite
|
Sign up to set email alerts
|

Congenital aphallia associated with congenital urethrorectal fistula

Abstract: Rationale:Aphallia is an extremely rare congenital malformation of unknown cause, with few reports in the literature. It is usually associated with other urogenital and gastrointestinal anomalies and is believed to be a result of either the absence of a genital tubercle or chromosome polymorphism. Herein, we describe an extremely rare case of congenital aphallia with congenital urethrorectal fistula and describe our treatment for this patient.Patient concerns:An 8-year-old boy was brought to our hospital by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Kian et al, 2022 [ 5 ] 14 months 2.7 kg Aphallia • Penile absent • OUE not detected • Passing urine from anus • Scrotum developed • Bilateral descended testes • USG: Hipoplasia left kidney, mild diffuse wall thickening of uninary bladder • CT Scan, IV contrast, Hipoplasia of left kidney • Rectal enema with soluble contrast: Vesico rectal fistula, normal anus closure 2. Luo et al, 2022 [ 6 ] 8 years old - Absence of penis • Penile absent • Orificium urethræ externum not detected • Passing urine from anus • Scrotum developed • Bilateral descended testes • Anterograde urography: Fistula urethrorectal • Echocardiography, electrocardiogram, Chest CT, USG Abdominal normal • Karyotype chromosome: 46,XY • Blood chemistry and hematology test: Normal limits • Urine analisys: Normal limit • Urethral exteriorization via perineal urethroplast • Planned nephalloplasty at the time of puberty (age 10–15 years) 3. Braun et al, 2022 [ 7 ] 3 years Old - “Aphallia, norectal malformation without fistula • Absent of phallus • Normally descended testes • Anorectal malformation • Perineal urethra • The renal and bladder ultrasound, CT Scan, IV contrast: Malrotated kidneys • Magnetic resonance imaging: No visualisation of the corpora cavernosa or corpus spongiosum, normal sacrum and spinal cord - • Colostomy during the neonatal period followed by posterior-sagittal anorectoplasty • Perineal urethral closure • Suprapubic catheter (SPC) placement 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kian et al, 2022 [ 5 ] 14 months 2.7 kg Aphallia • Penile absent • OUE not detected • Passing urine from anus • Scrotum developed • Bilateral descended testes • USG: Hipoplasia left kidney, mild diffuse wall thickening of uninary bladder • CT Scan, IV contrast, Hipoplasia of left kidney • Rectal enema with soluble contrast: Vesico rectal fistula, normal anus closure 2. Luo et al, 2022 [ 6 ] 8 years old - Absence of penis • Penile absent • Orificium urethræ externum not detected • Passing urine from anus • Scrotum developed • Bilateral descended testes • Anterograde urography: Fistula urethrorectal • Echocardiography, electrocardiogram, Chest CT, USG Abdominal normal • Karyotype chromosome: 46,XY • Blood chemistry and hematology test: Normal limits • Urine analisys: Normal limit • Urethral exteriorization via perineal urethroplast • Planned nephalloplasty at the time of puberty (age 10–15 years) 3. Braun et al, 2022 [ 7 ] 3 years Old - “Aphallia, norectal malformation without fistula • Absent of phallus • Normally descended testes • Anorectal malformation • Perineal urethra • The renal and bladder ultrasound, CT Scan, IV contrast: Malrotated kidneys • Magnetic resonance imaging: No visualisation of the corpora cavernosa or corpus spongiosum, normal sacrum and spinal cord - • Colostomy during the neonatal period followed by posterior-sagittal anorectoplasty • Perineal urethral closure • Suprapubic catheter (SPC) placement 4.…”
Section: Resultsmentioning
confidence: 99%
“…The most cases were reported in the USA which were 31% (n:13) of all cases [ 2 , 7 , 8 , 12 , 16 , 30 , 32 34 ], followed by India with 21% (n:9) [ 14 , 18 , 19 , 21 , 25 , 29 , 34 ] Iran with 12% (n:5) [ 5 , 13 , 17 ], China with 7.3% [ 1 , 6 , 23 ], Turkey with 4% (n:2) [ 15 , 31 ], France with 4% (n:2) [ 23 , 27 ], Japan with 4% (n:2) [ 26 , 27 ], Morocco with 4% (n:2) [ 9 , 10 ], Mexico with 2% (n:1) [ 3 ], UK with 2% (n:1) [ 11 ], and Senegal with 2% (n:1) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Qiang et al (2019) found chromosome 9 heterochromatin (9 qh +) was responsible for the protective function and regulation of hereditary diseases and susceptibility to congenital disease from the father of aphallia's patients (Qiang et al, 2019). Consistently Luo study showed that congenital aphallia is associated with congenital urethrorectal fistula which is regulated by the same chromosome (Luo et al, 2022) Another examination to identify male fertility is whether there is a deletion or not on the Y chromosome that causes significant failure of spermatogenesis. The gene responsible for human spermatogenesis is the AZF locus.…”
Section: Discussionmentioning
confidence: 95%